Modeling growth curves for Indian Native vs Exotic chicken breeds to assist in selection strategies - YADAV, S P; SARKAR, S K; MAHAPATRA, R K; KANNAKI, T R; DANGE, M; BHATTACHARYA, T K; CHATTERJEE, R N (The Indian Journal of Animal Sciences, 2019)
The knowledge of growth curves in poultry is worth for determining economic efficiencies. With the availability of advance and potent computing algorithm, we can develop suitable statistical procedures for model evaluation which suites for the estimation of parameters influencing body weight in native and exotic chicken breeds. In this study, three breeds of chicken . Brown Nicobari (119), Ghagus (118) and Dahlem Red (125) were taken which were hatched at the same time using 20 sires and eighty dams from each breed and maintained at ICAR-Directorate of Poultry Research, Hyderabad under same milieu. Genetic parameters, for body weight up to 14 weeks of age, of all the three breeds have been evaluated. Data on parameters like egg weight (at the time of incubation), birth weight and weight at weekly intervals up to 14 weeks of age were recorded. The animal growth data are generally non-linear in nature so an attempt has been made to fit non-linear growth models, viz. exponential, logistic, Gompertz and monomolecular on data pertaining to body weight of native and exotic poultry breeds. The study concludes that the two criteria Mean Absolute Error and Root Mean Square Error support the logistic model which was found to be most suitable growth model for poultry birds.